2018
DOI: 10.1186/s12888-018-1607-0
|View full text |Cite
|
Sign up to set email alerts
|

A self-harm series and its relationship with childhood adversity among adolescents in mainland China: a cross-sectional study

Abstract: BackgroundSelf-harm (SH) is an emerging problem among Chinese adolescents. The present study aimed to measure the prevalence of SH behaviours and to explore the relationship between childhood adversity and different SH subtypes among Chinese adolescents.MethodsA total of 5726 middle school students were randomly selected in three cities of Anhui province, China, using a stratified cluster sampling method. SH was categorized into five subtypes (highly lethal self-harm, less lethal self-harm with visible tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
2
28
1
2
Order By: Relevance
“…Self-harm was associated with drinking behaviors in both boys and girls. The Log-binomial regression demonstrated that girls in [16][17][18][19] years were at lower risk of self-harm than girls in 12-15 years while this association was weaker in boys (1.493 vs 1.128). The higher OR for self-harm was found among girls with early drinking experiences compared with boys (2.565 vs 1.863).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Self-harm was associated with drinking behaviors in both boys and girls. The Log-binomial regression demonstrated that girls in [16][17][18][19] years were at lower risk of self-harm than girls in 12-15 years while this association was weaker in boys (1.493 vs 1.128). The higher OR for self-harm was found among girls with early drinking experiences compared with boys (2.565 vs 1.863).…”
Section: Resultsmentioning
confidence: 94%
“…Within the lifecourse, self-harm is the most prevalent when it comes to puberty [9]. Globally, the prevalence of self-harm ranged from 3.1% to 15.5 % among adolescents aged between 12 to 21 years[3, 4, 10-15], while in China, the prevalence reached 27.6% and some subtypes of self-harm could be even at 32.0% [5,16]. This higher self-harm prevalence might be mainly interpreted by academic-related stress due to the competitiveness in the education system [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several past and present studies validate the study results that exposure to adverse childhood experiences (ACE) subsequently leads to the adoption of smoking ( 41 ) and early alcohol use among adolescents ( 42 ). Also, an alarming rate of suicide attempts ( 43 ) and non-suicidal self-harm (NSSH) is attributed to early childhood trauma ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the lifecourse, self-harm is more prevalent when it comes to puberty [9]. Globally, the prevalence of self-harm ranged from 3.1% to 15.5 % among adolescents aged between 12 to 21 years [1,5,[10][11][12][13][14][15], while in China, the prevalence reached 27.6% and some subtypes of self-harm could be even at 32.0% [2,16]. An 'iceberg model' is often raised to describe the situation of suicide, so is the self-harm, which is recognized as a 'hidden behavior': less than 13% of the self-harm episodes led to hospital presentation [1,7,10].…”
Section: Introductionmentioning
confidence: 99%